2009
DOI: 10.1210/me.2008-0260
|View full text |Cite
|
Sign up to set email alerts
|

A Preformed Signaling Complex Mediates GnRH-Activated ERK Phosphorylation of Paxillin and FAK at Focal Adhesions in LβT2 Gonadotrope Cells

Abstract: Most receptor tyrosine kinases and G protein-coupled receptors (GPCRs) operate via a limited number of MAPK cascades but still exert diverse functions, and therefore signal specificity remains an enigma. Also, most GPCR ligands utilize families of receptors for mediation of diverse biological actions; however, the mammalian type I GnRH receptor (GnRHR) seems to be the sole receptor mediating GnRH-induced gonadotropin synthesis and release. Signaling complexes associated with GPCRs may thus provide the means fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 80 publications
1
33
0
Order By: Relevance
“…5) and also ERK (36,37) downstream of G q PCRs. These differences in c-Src effects before and after stimulation could be a result of an alternative complex formation, as recently reported upon GnRH-a nonapoptotic stimulation of L␤T2 cells (38). Alternatively, it can also be due to interference by interacting downstream processes, such as phosphatases or additional inhibitory phosphorylations.…”
Section: Discussionmentioning
confidence: 63%
“…5) and also ERK (36,37) downstream of G q PCRs. These differences in c-Src effects before and after stimulation could be a result of an alternative complex formation, as recently reported upon GnRH-a nonapoptotic stimulation of L␤T2 cells (38). Alternatively, it can also be due to interference by interacting downstream processes, such as phosphatases or additional inhibitory phosphorylations.…”
Section: Discussionmentioning
confidence: 63%
“…5) and also ERK [42,43] downstream of GqPCRs. These differences in c-Src effects before and after stimulation could be a result of an alternative complex formation, as recently reported upon GnRH-a non-apoptotic stimulation of LβT2 cells [44]. Alternatively, it can also be due to interference by interacting downstream processes, such as phosphatases or additional inhibitory phosphorylations.…”
Section: Discussionmentioning
confidence: 65%
“…4). Previous studies (40,41,61) also suggested that paxillin might function as a scaffold to hold Raf, MEK, and Erk1/2 in a signaling complex. Most of these studies (17, 40 -42, 61, 62) focused on the association of paxillin with focal adhesion molecules, using overexpression and co-precipitation studies to show interactions.…”
Section: Discussionmentioning
confidence: 95%